Psychotropic Polypharmacy and the Medicalization of Life in a Psychosocial Care Center with alcohol and other drugs in the Federal District - Silva, Sara Ângela (2023)
Psychotropic drugs emerged after World War II as a revolution for the treatment of mental disorders and treated as essential for Psychiatric Reform. But from the prescription of different drugs, there is the possibility of occurrence of psychotropic polypharmacy, which is more commonly defined as the concomitant use of 2 or more psychotropic drugs. During clinical practice, it was possible to observe a high number of prescriptions, which allows an association with the criticism of the medicalization of life and, consequently, the medicationization of suffering. The objective of this study was to analyze the association between medicalization and medicationization in psychiatry and the presence of psychotropic polypharmacy for user of a Psychosocial Care Center with alcohol and other drugs (CAPS AD). It is a cross-sectional study and descriptive analysis. The method was analysis of data collected from medical records of users of a CAPS AD III in the Federal District during the year 2021. The data were launched in a Microsoft Excel® and analyzed quantitatively. The occurrence of psychotropic polypharmacy was identified in 100% of the analyzed sample, with the use of 2 to 6 medications per user. In all, the study participants were using 24 different psychotropic drugs, with the highest prevalence being Naltrexone, a standardized drug for exclusive use in the treatment of addiction. Potential drug interactions (PIM) were also identified in 90.9% of the sample, an event whose main risk factor is polypharmacy. Thus, it was possible to observe the importance of an effective psychosocial attendance, to optimize the results and a need for pharmaceutical attendance, to evaluate the therapeutic efficacy and to carry out monitoring and review of the pharmacotherapy.